Determination of zinc compounds in yeast biomass - Thi Trang, Nguyen; Thi Minh Khanh, Nguyen; Duc Manh, Le; Thoa, Vu Kim; Dinh Binh, Chu; Thi Lan Anh, Pham (Vietnam Journal of Biotechnology, 2020)
Zinc is an essential trace element for many physiological function in human and animal. When bound to organic substrate, zinc is more efficiently absorbed by organisms, has a high biological activity and a low toxicity. The ability of S. cerevisiae to accumulate zinc can be used for production of a zinc-rich ingredient for functional food products. However, only a few investigations on the form of Zn in S. cerevisiae have been reported. In this study, organic and inorganic compounds of zinc in yeast extract samples was separated on D101 macro-resin and quantified by inductively coupled plasma mass spectrometry (ICP-MS). Inorganic and organic compounds of zinc in yeast samples were extracted with photphate buffer by bead mills method and fractionated on the D101 macro-resin. All critical parameters of extraction conditions as well as separation conditions of zinc compounds on D101 macro-resin were investigated and optimized. In addition, speciation analysis of zinc compounds also was performed with online high-performance ion chromatography in combination with inductively coupled plasma mass spectrometry (HPIC-ICP-MS). Analyzed results indicated that the content of the organic state of Zn was more than that of the inorganic state. Organic zinc was the most abundance in yeast samples in the 51.56 – 88.17%. The highest organic zinc was found in S. cerevisiae A112 at 88.17%. In all of the samples, the organic zinc was found in the polysaccharide fraction was more than that of protein fraction. Our research results are significant for medical and food applications. Speciation analysis of trace element Zn is helpful to elucidate its pharmacological mechanism